Production of Bioethanol from Cordia dichotoma and Physalis minima - Jayamma, P.; Shareef, S. Baba; Shamshuddin, Md.; Sandhya, P. Sai; Manjula, B. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted from September, 2022 to June, 2024 in the Department of Food Safety and Quality Assurance, College of Food Science and Technology, Acharya N. G. Ranga Agricultural University, Pulivendula. Bioethanol, an eco-friendly and renewable biofuel, can be efficiently produced from agricultural and fruit wastes. The present study aimed to produce bioethanol from the fruits of Cordia dichotoma and Physalis minima, which are abundantly available, cost-effective, and underutilized. Twelve yeast isolates were obtained from fruit wastes such as banana, apple, sapota, jamun, jackfruit, dragon fruit, pineapple, pomegranate, grapes, guava, papaya, and mango, collected under sterile conditions. The isolates were identified as yeasts based on morphological and biochemical characteristics. Sugar utilization tests revealed that all isolates fermented glucose, fructose, and sucrose, while only some (CAY, MY, DFY, JY, PGY, SY, BY) utilized maltose. Among them, isolates CAY, MY, and BY showed the highest ethanol yields with reduced residual sugars during glucose fermentation and were selected for further fermentation studies using Physalis minima and Cordia dichotoma powders as substrates. The CAY isolate exhibited maximum fermentation efficiency, producing 18.644 g l-1 ethanol from Physalis minima and 28.024 g l-1 from Cordia dichotoma, with minimal residual sugars. These findings indicate that Cordia dichotoma and Physalis minima fruits can serve as promising, low-cost substrates for sustainable bioethanol production, contributing to renewable energy development and reducing reliance on fossil fuels.